Metal Composite Core

The metal composite core, made of ferrite and soft magnetic metal powders, addresses shape and efficiency issues in coil components by maintaining high permeability and low iron loss without high-pressure molding, enhancing coil performance and flexibility.

JP7623329B2Active Publication Date: 2025-01-28TAMURA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022147078
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-01-28
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

Existing coil components, particularly those using pressure porcelain cores, face limitations in shape flexibility and energy efficiency due to high-pressure molding, which affects magnetic properties such as permeability and iron loss.

Method used

A metal composite core composed of a mixture of ferrite powder and soft magnetic metal powder, with specific particle size and ratio, is used to create a magnetic material that can be molded easily and maintains high permeability and low iron loss without high-pressure molding.

Benefits of technology

The composite core achieves high permeability, low iron loss, and stable magnetic characteristics, suitable for coil components, while allowing for flexible shaping and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623329000006
    Figure 0007623329000006
  • Figure 0007623329000007
    Figure 0007623329000007
  • Figure 0007623329000008
    Figure 0007623329000008
Patent Text Reader

Abstract

To provide a composite magnetic material which has high magnetic permeability, low iron loss, and stable magnetic characteristics.SOLUTION: A composite magnetic material contains magnetic powder formed by mixing ferrite powder and soft magnetic metal powder, and a resin. A particle diameter of the ferrite powder is 395 μm or more. An addition amount of the ferrite powder is 5 wt.% or more and 20 wt.% or less with respect to the soft magnetic metal powder. Preferably, a particle diameter of the ferrite powder is larger than that of the soft magnetic metal powder, and the upper limit value is 890 μm. When 5.0 wt.% of the ferrite powder is added thereto, as compared to a case where the ferrite powder is not added thereto, initial permeability is high, eddy current loss is reduced, and iron loss is reduced. Therefore, when 5 wt.% or more of the ferrite powder is added thereto, magnetic permeability becomes high and iron loss becomes low, and magnetic characteristics become stable.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite magnetic material containing a magnetic powder formed by mixing ferrite powder and soft magnetic metal powder. [Background technology]

[0002] Coil components such as reactors are used in a variety of applications, including office equipment, solar power generation systems, and automobiles. Coil components have a coil attached to a core. Powder magnetic cores are often used for this core.

[0003] Powder cores are formed by pressure molding soft magnetic powder and an insulating coating that covers the soft magnetic powder. The pressure during this pressure molding is quite high, ranging from several tons to several tens of tons, to compress the magnetic powder. Therefore, powder cores can only be manufactured in shapes that can withstand this pressure, and there are restrictions on the shape. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-199568 A Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, metal composite cores made by hardening a composite magnetic material made by mixing magnetic powder and resin are attracting attention. The composite magnetic material is clay-like. Therefore, it is easy to pour the composite magnetic material into every corner of a container. Therefore, it can be molded to fit the shape of the container, and the degree of freedom of the core shape is higher than that of powder magnetic cores.

[0006] On the other hand, because they are used as the cores of coil components, they also require improved magnetic properties to improve energy exchange efficiency and reduce heat generation. Examples of magnetic properties include magnetic permeability, which allows a large magnetic flux density to be obtained with a small applied magnetic field, and iron loss, which means that the energy loss caused by changes in magnetic flux density is small. Iron loss is expressed as the sum of hysteresis loss and eddy current loss.

[0007] In recent years, there has been an increasing demand for environmentally friendly electronic devices with smaller size and higher performance, and as a result, there is a particular demand for stable magnetic properties, including high permeability and low core loss, rather than simply improving either the permeability or the core loss.

[0008] The present invention has been proposed to solve the above problems, and an object of the present invention is to provide a composite magnetic material that has high magnetic permeability, low core loss, and stable magnetic properties. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention Metal Composite Core is a magnetic powder made by mixing ferrite powder and soft magnetic metal powder. Metal composite core with resin mixed in The ferrite powder has a particle diameter of 395 μm or more, and the amount of the ferrite powder added is 5 wt % or more and 20 wt % or less with respect to the soft magnetic metal powder. Effect of the Invention

[0010] According to the present invention, a composite magnetic material having high magnetic permeability, low core loss, and stable magnetic properties can be obtained. [Brief description of the drawings]

[0011] [Figure 1] 1 is a graph showing the relationship between the magnetic field and the magnetic permeability in Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 2] 1 is a graph showing the relationship between the amount of ferrite powder added and core loss in Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 3]1 is a graph showing the relationship between the magnetic field and the magnetic permeability in Examples 4 to 6 and Comparative Example 3. [Figure 4] 1 is a graph showing the relationship between the amount of ferrite powder added and core loss in Examples 4 to 6 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Embodiment) The configuration of the composite magnetic material and metal composite core (hereinafter also referred to as MC core) of this embodiment will be described. The MC core of this embodiment is formed by filling a specified container with the composite magnetic material and hardening it. The composite magnetic material is clay-like. Therefore, the composite magnetic material can be poured into every corner of the container. Therefore, it is easy to mold it according to the shape of the container, and the MC core can be molded into a desired shape. This MC core is used as a magnetic body for coil parts such as reactors.

[0013] Composite magnetic materials are composed of magnetic powder and resin. The magnetic powder is made of a mixed powder of ferrite powder and soft magnetic metal powder. By mixing in insulating ferrite powder, it is possible to ensure insulation between the soft magnetic metal powder and reduce iron loss, while at the same time obtaining high magnetic permeability due to the magnetism of the ferrite powder. Mixing can be done using a mixer (W-type, V-type), a pot mill, etc.

[0014] The ferrite powder may be, for example, a spinel ferrite. Examples of the spinel ferrite include Mn-Zn ferrite, Ni-Zn ferrite, Cu-Zn ferrite, Ni-Cu-Zn ferrite, Mn-Cu-Zn ferrite, and Ni-Mn-Cu-Zn ferrite. In the present embodiment, Mn-Zn ferrite is used.

[0015] The particle size of the ferrite powder is preferably larger than that of the soft magnetic metal powder. In particular, the particle size of the ferrite powder is preferably at least twice as large as that of the soft magnetic metal powder. In other words, the particle size of the soft magnetic metal powder is smaller than that of the ferrite powder. If a soft magnetic metal powder with a large particle size is used, there is a risk of increased eddy current loss.

[0016] Specifically, the particle diameter (median diameter D50) of the ferrite powder is 395 μm or more. By using ferrite powder with a large particle diameter, such as ferrite powder with a particle diameter (median diameter D50) of 395 μm or more, it is possible to ensure the insulation distance between the soft magnetic metal powders, and to manufacture an MC core with a good balance of high density, high magnetic permeability, and low iron loss. In addition, the particle diameter (median diameter D50) of the ferrite powder is preferably 890 μm or less. If it exceeds 890 μm, the manufacturing cost will be high.

[0017] The ferrite powder is preferably as close to spherical as possible. In other words, the circularity of the ferrite powder is preferably 0.93 or more. By using ferrite powder with a circularity of 0.93 or more, the magnetic permeability can be increased.

[0018] The amount of ferrite powder added is between 5wt% and 20wt% of the soft magnetic metal powder. If it is less than 5wt%, the ferrite powder content is low, making it difficult to obtain the effects of high density, high magnetic permeability, and low iron loss. On the other hand, if it is more than 20wt%, the initial magnetic permeability is high, but the magnetic permeability decreases when superimposed, and the rate of reduction in magnetic permeability is large. This is thought to be because the ferrite powder has a lower magnetic flux density and therefore saturates first, while the soft magnetic metal powder content is low, reducing the magnetic permeability when superimposed.

[0019] The soft magnetic metal powder is attached to the periphery of the ferrite powder, but the manner of attachment is not important. In other words, the soft magnetic metal powder may be attached so as to cover the entire periphery of the ferrite powder, or may be attached so as to cover a part of the periphery of the ferrite powder, with a part of the surface of the ferrite powder being exposed. The soft magnetic metal powder may be attached to the surface of each particle of the ferrite powder, or may be attached to the surface of an aggregate of the ferrite powder, or may be attached in a manner in which these attachment modes are mixed. Furthermore, the ferrite powder may be attached in such a manner that it is interposed between the soft magnetic metal powders.

[0020] The soft magnetic metal powder may be Fe powder, Fe-Si alloy powder, Fe-Al alloy powder, Fe-Si-Al alloy powder (Sendust), amorphous alloy powder, nanocrystal, or a mixture of two or more of these powders. For example, Fe-6.5% Si alloy powder or Fe-3.5% Si alloy powder may be used as the Fe-Si alloy powder. When two or more types of powders are used as the soft magnetic metal powder, the types may be the same or different. Even when the same type of powder is used as the soft magnetic metal powder, the particle size of each powder may be changed to make two types.

[0021] When using powders with different particle sizes as the soft magnetic metal powder, the particle size (median size D50) of the larger soft magnetic metal powder is preferably 100 μm to 200 μm, and the particle size (median size D50) of the smaller soft magnetic metal powder is preferably 3 μm to 10 μm. By setting the particle size of each soft magnetic metal powder within this range, the smaller soft magnetic metal powder can easily enter the gaps between the larger soft magnetic metal powder, improving the density and magnetic permeability and reducing iron loss. In addition, when using powders with two different particle sizes as the soft magnetic metal powder, the particle size relationship with the ferrite powder is based on the soft magnetic metal powder with the larger particle size.

[0022] In addition, when using two types of soft magnetic metal powders with different particle sizes, the weight ratio of the larger particle size soft magnetic metal powder to the smaller particle size soft magnetic metal powder is preferably 80:20 to 60:40. By setting the ratio in this range, the density and magnetic permeability can be improved and the iron loss can be reduced.

[0023] The resin that constitutes the composite magnetic material is mixed with the magnetic powder and is present between the magnetic powder particles. More specifically, the resin does not cover the magnetic powder particles, but fills the gaps between the magnetic powder particles. The addition of the resin bonds the magnetic powder particles together.

[0024] The resin may be a thermosetting resin, an ultraviolet curing resin, or a thermoplastic resin. The thermosetting resin may be a phenolic resin, an epoxy resin, an unsaturated polyester resin, a polyurethane, a diallyl phthalate resin, a silicone resin, or the like. The ultraviolet curing resin may be a urethane acrylate-based, an epoxy acrylate-based, an acrylate-based, or an epoxy-based resin. The thermoplastic resin may be a resin having excellent heat resistance, such as a polyimide or a fluororesin.

[0025] The resin content is preferably 3 to 5 wt% relative to the magnetic powder. If the resin content is less than 3 wt%, the bonding strength of the magnetic powder is insufficient, and the mechanical strength of the MC core is reduced. If the resin content is more than 5 wt%, the magnetic powder cannot be held without gaps, and the density of the MC core is reduced, resulting in a decrease in magnetic permeability.

[0026] The resin may contain a filler. By adding the filler, the viscosity of the composite magnetic material can be adjusted. The filler is Al. 2 O 3 , BN, AlN, SiO 2 , Fe 2 O 3 , ZnO, TiO 2 etc. can be used.

[0027] The composite magnetic material, which is a mixture of magnetic powder and resin, is filled into a specified container and the resin is hardened to form an MC core. When manufacturing an MC core, pressure molding, as is the case with powder magnetic cores, is not an essential requirement, so after filling the container with the composite magnetic material, the process may move on to the hardening step without pressure molding.

[0028] In addition, even if a pressurizing process is performed after filling the composite magnetic material in a container, the pressure is set to more than 0 to 16 kg / cm during the manufacture of the MC core. 2 In other words, a low pressure of several tons / cm2 to several tens of tons / cm2 is sufficient, as in the case of powder magnetic cores. 2 Therefore, unlike a dust core, where the magnetic powder deforms, the magnetic powder in an MC core does not deform even when pressure is applied.

[0029] In this way, dust cores are compressed with high pressure, and this compression can improve their properties, such as increasing their density. In other words, the properties of the magnetic powder are also based on the assumption that they are compressed with high pressure. On the other hand, MC cores are not compressed, or if compressed, the pressure is low, so the properties of the magnetic powder are directly linked to the properties of the MC core. In other words, it is important to improve the properties of the magnetic powder itself, without considering the improvement of properties by compression as in dust cores. Therefore, dust cores and MC cores have different approaches to the production of magnetic powder, and the technology used for dust cores cannot be simply transferred to MC cores.

[0030] After the composite magnetic material is filled into a container, or after the composite magnetic material filled into a container is pressure-molded, a resin curing process is performed to harden the resin. The MC core is produced through this resin curing process. The resin may be cured by an appropriate method depending on the type of resin.

[0031] For example, when the resin is cured by drying under heat, the drying atmosphere can be an air atmosphere. The drying time can be appropriately changed depending on the type, content, drying temperature, etc. of the resin, but can be, for example, 1 hour to 4 hours. The drying temperature can be appropriately changed depending on the type, content, drying time, etc. of the resin, but can be, for example, 85°C or higher and 200°C or lower.

[0032] On the other hand, as mentioned above, dust cores are compacted under high pressure, which creates distortion inside the magnetic powder. For this reason, in the production of dust cores, a heat treatment called annealing is carried out after compaction. This annealing is carried out at a high temperature of 600°C or higher to remove distortion. If heat treatment is carried out at such a high temperature, the properties of the ferrite powder will deteriorate. However, in the case of MC cores, the resin curing process is carried out at a low temperature of 200°C or lower, so the properties of the ferrite powder do not deteriorate and can be maintained.

[0033] (First embodiment) Next, the present invention will be described in more detail based on examples. Note that the present invention is not limited to the following examples. MC cores of Examples 1 to 3 and Comparative Examples 1 and 2 were produced as follows.

[0034] In Example 1, a mixed powder of ferrite powder and soft magnetic metal powder was used as the magnetic powder. Mn-Zn ferrite was used as the ferrite powder. The particle size of the ferrite powder was 890 μm, which is indicated by the particle size D50 shown in Type A of Table 1 below. As the soft magnetic metal powder, FeSi alloy powder was used as shown in Table 1. Two types of FeSi alloy powder with different particle shapes were prepared, one of which had an average particle size (D50) of 149 μm (hereinafter, sometimes referred to as "first metal powder") and the other had an average particle size (D50) of 6 μm (hereinafter, sometimes referred to as "second metal powder"). The ratio of the first metal powder to the second metal powder was 70:30.

[0035] [Table 1]

[0036] A mixed powder was prepared by adding 5.0 wt% of ferrite powder and 95 wt% of soft magnetic metal powder. 4.0 wt% of epoxy resin was added to the mixed powder as a resin and mixed to prepare a composite magnetic material.

[0037] After mixing the epoxy resin, the mixture was filled into a case having an outer diameter of 26.0 mm, an inner diameter of 15.2 mm, and a height of 6.5 mm without pressure molding, and then heated at a temperature of 150° C. for 4 hours to harden the resin, thereby producing the MC core of Example 1.

[0038] Examples 2 and 3 and Comparative Examples 1 and 2 differ from Example 1 only in the amount of ferrite powder added (see Table 2), and the other materials used, the manufacturing procedure, and the manufacturing conditions are the same as those of Example 1. Note that Comparative Example 1 does not use ferrite powder as the magnetic powder, and instead uses a mixed powder in which only the first metal powder and the second metal powder are mixed.

[0039] The density, magnetic permeability, and hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured.

[0040] The density is the apparent density. That is, the outer diameter, inner diameter, and height of each MC core are measured, and the volume (cm 3 ) into π×(outer diameter 2 -Inner diameter 2 The mass of each MC core was measured, and the density of the MC core was calculated by dividing the measured mass by the calculated volume.

[0041] When measuring each magnetic permeability, two copper wires with a diameter of 0.5 mm were wound in parallel around the MC core, and wound 30 turns as the primary winding. Then, using an LCR meter (Hewlett Packard: 4284A), the initial magnetic permeability (0 A / m) and the magnetic permeability at 4.9 kA / m were calculated from the inductance of the magnetic field strength at 100 kHz and 1.0 V. The reduction rate at the time of superposition was also calculated by dividing the calculated magnetic permeability at 4.9 kA / m by the initial magnetic permeability.

[0042] For the iron loss measurement, 30 turns of φ0.5mm copper wire were wound around the MC core as the primary winding and 31 turns as the secondary winding. Then, using a BH analyzer (Iwatsu Measurement Corporation: SY-8219), a magnetic measuring device, the iron loss Pcv (kW / m 3 ) was measured. The hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3 ) was calculated. Hysteresis loss Ph (kW / m 3 ) and eddy current loss Pe(kW / m 3 ) was performed by calculating the hysteresis loss coefficient (Kh) and eddy current loss coefficient (Ke) from the frequency curve of iron loss Pcv using the following equations (1) to (3) by the least squares method.

[0043] Pcv = Kh×f + Ke×f 2 (1) Ph = Kh × f (2) Pe = Ke × f 2 (3) Pcv: Iron loss Kh: Hysteresis loss coefficient Ke: Eddy current loss coefficient f: frequency Ph: Hysteresis loss Pe: Eddy current loss

[0044] The measurement results are shown in Table 2. A graph showing the relationship between the amount of ferrite powder added and the core loss in Examples 1 to 3 and Comparative Examples 1 and 2 is shown in Figure 1, and a graph showing the relationship between the magnetic field and the magnetic permeability in Examples 1 to 3 and Comparative Examples 1 and 2 is shown in Figure 2. In Figure 2, the Examples are shown by a solid line, and the Comparative Examples are shown by a dashed line.

[0045] [Table 2]

[0046] As shown in Table 2 and Fig. 1, Example 1, in which 5.0 wt% ferrite powder was added, had a higher initial permeability, a reduced eddy current loss, and a reduced iron loss, compared to Comparative Example 1, in which no ferrite powder was added. Furthermore, in Example 1, the permeability at 4.9 kA / m during superposition did not decrease significantly compared to Comparative Example 1. Therefore, it was confirmed that the addition of 5 wt% or more ferrite powder resulted in high permeability and low iron loss, and stable magnetic properties.

[0047] As the amount of ferrite powder added increases, the initial permeability increases, but the permeability gradually decreases from 4.9 kA / m, and in Comparative Example 2, where 40 wt% was added, the permeability was 25.0, and the rate of decrease when superimposed was also 0.49, a large decrease from the initial permeability. Therefore, it was confirmed that setting the upper limit of the amount of ferrite powder added to 20 wt% resulted in high permeability, low iron loss, and stable magnetic properties. From the above points, it was confirmed that the amount of ferrite powder added should be between 5 wt% and 20 wt%.

[0048] Also, as shown in FIG. 2, when the magnetic field exceeds 7000 (A / m), the magnetic permeability of Examples 1 to 3 is lower than that of Comparative Example 1, in which no ferrite powder is added. However, reactors using the MC core of the present invention are often used in magnetic fields of 5000 (A / m). Examples 1 to 3 maintain good magnetic permeability in a magnetic field of 5000 (A / m). Therefore, it was confirmed that they are suitable for reactors used in a magnetic field of 5000 (A / m).

[0049] (Second Example) Next, MC cores were produced for Examples 4 to 6 and Comparative Example 3, in which the type of ferrite powder was changed from that of Example 1. Specifically, in Example 1, ferrite powder of type A shown in Table 1 and having a particle size of 890 μm (D50) was used, whereas in Examples 4 to 6 and Comparative Example 3, ferrite powder of type B shown in Table 1 and having a particle size of 395 μm (D50) was used.

[0050] The amounts of ferrite powder added in Examples 4 to 6 and Comparative Example 3 are as shown in Table 3 below. Other materials used, manufacturing procedures, and manufacturing conditions were the same as in Example 1. The density, magnetic permeability, and hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured in the same manner as in the first example.

[0051] The measurement results are shown in Table 3. A graph showing the relationship between the amount of ferrite powder added and the core loss in Examples 4 to 6 and Comparative Example 3 is shown in Fig. 3, and a graph showing the relationship between the magnetic field and the magnetic permeability in Examples 4 to 6 and Comparative Example 3 is shown in Fig. 4. In Fig. 4, the examples are shown by a solid line, and the comparative examples are shown by a dashed line.

[0052] [Table 3]

[0053] 3, Example 4, in which 5.0 wt% of ferrite powder having a particle size of 395 μm was added, had improved initial permeability and permeability of 4.9 kA / m and reduced iron loss compared to Comparative Example 1, in which no ferrite powder was added. Example 5 and Example 6, in which the amount of ferrite powder added was 10.0 wt% and 20.0 wt%, also had high initial permeability and permeability of 4.9 kA / m and low iron loss.

[0054] On the other hand, in Comparative Example 3, in which 40.0 wt% of ferrite powder was added, the initial permeability was the same as that of Comparative Example 1, but the permeability of 4.9 kA / m was greatly reduced, and the hysteresis loss increased, leading to an increase in iron loss. Therefore, even if the particle size of the ferrite powder was changed, it was confirmed that when the amount of ferrite powder added was 5 wt% or more and 20 wt% or less, high permeability and low iron loss were achieved, resulting in stable magnetic properties. Also, as shown in FIG. 4, it was confirmed that Examples 4 to 6 maintained good permeability in a magnetic field of 5000 (A / m).

[0055] (Third Example) An MC core of Comparative Example 4 was produced using a different type of ferrite powder from that of Example 1. Specifically, in Example 1, ferrite powder of type A shown in Table 1 with a particle size of 890 μm (D50) was used, whereas in Comparative Example 4, ferrite powder of type C with a particle size of 15 μm (D50) was used.

[0056] In Comparative Example 4, 10.0 wt% of ferrite powder having a particle size of 15 μm and 90.0 wt% of soft magnetic metal powder (first metal powder and second metal powder) were added. The other materials used, the manufacturing procedure, and the manufacturing conditions were the same as those in Example 1. The density, magnetic permeability, and hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured in the same manner as in the first example.

[0057] The measurement results are shown in Table 4. [Table 4]

[0058] As shown in Table 4, the initial permeability and the permeability at 4.9 kA / m of Comparative Example 4 are worse than those of Comparative Example 1 in which no ferrite powder was added. Furthermore, although the eddy current loss of Comparative Example 4 is lower than that of Comparative Example 1, the hysteresis loss is significantly increased, and therefore the iron loss is also worse than that of Comparative Example 1.

[0059] In addition, even when compared with Examples 2 and 5 in which 10 wt% ferrite powder was added, which is the same amount as in Comparative Example 4, Examples 2 and 5 have improved initial permeability, permeability at 4.9 kA / m, and iron loss compared to Comparative Example 4.

[0060] From this, it was confirmed that using ferrite powder with a small particle size as the magnetic powder is ineffective. In other words, taking into consideration the first and second examples as well, it was confirmed that when the particle size of the ferrite powder is 395 μm or more, high magnetic permeability and low iron loss can be achieved.

[0061] (Fourth Example) Next, an MC core of Comparative Example 5 was produced. For the MC core of Comparative Example 5, no soft magnetic metal powder was used as the magnetic powder, and instead a magnetic powder consisting of only two types of ferrite powder, types B and C, shown in Table 1, was used. A mixed powder was produced by adding 70 wt% of type B ferrite powder and 30 wt% of type C ferrite powder. The other materials used, the production procedure, and the production conditions were the same as in Example 1. The density, magnetic permeability, and hysteresis loss (kW / m 3 ), eddy current loss (kW / m 3 ) and iron loss (kW / m 3 ) was measured in the same manner as in the first example.

[0062] The measurement results are shown in Table 5. [Table 5]

[0063] Comparative Example 5, which was made only of ferrite powder, had an initial permeability of 32, a permeability at 4.9 kA / m of 18.7, and a drop rate at the time of superposition of 0.58, which is lower than that of Comparative Example 1, which was made only of soft magnetic metal powder. In addition, the iron loss was also 340 (kW / m 3) which is a value larger than that of Comparative Example 1. In other words, Comparative Example 5 results in both worse magnetic permeability and iron loss than Examples 1 to 6. In this way, it was confirmed that by using a mixed powder of ferrite powder and soft magnetic metal powder, rather than using only ferrite powder, as the magnetic powder, it is possible to obtain the effect of high magnetic permeability and reduced iron loss.

[0064] (Other embodiments) In this specification, an embodiment of the present invention has been described, but this embodiment is presented as an example and is not intended to limit the scope of the invention. The above-mentioned embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention.

Claims

1. A metal composite core in which a resin is mixed with magnetic powder made of a mixture of ferrite powder and soft magnetic metal powder, The particle size of the ferrite powder is 395 μm or more, The amount of the ferrite powder added is 5 wt % or more and 20 wt % or less with respect to the soft magnetic metal powder; Featuring a metal composite core.

2. The particle size of the ferrite powder is 890 μm or less; The metal composite core according to claim 1 .

3. The particle size of the ferrite powder is larger than the particle size of the soft magnetic metal powder; 3. The metal composite core according to claim 1 or 2.

4. The particle size of the ferrite powder is at least twice the particle size of the soft magnetic metal powder; The metal composite core according to claim 3 .

Citation Information

Patent Citations

  • Microwave absorver

    JP1977019046A

  • Plastic composition containing ferrite

    JP1991064005A

  • Compound-type pressed powder magnetic core and its manufacture

    JP1992242903A

  • Powder molded magnetic core

    JP2000294418A

  • Anisotropic bonded magnet, rotating machine, and magnet roll

    JP2002164206A